Novel mutation in NIPAL4 in a Romanian family with autosomal recessive congenital ichthyosis. (1st April 2016) - Maier, D.; Mazereeuw‐Hautier, J.; Tilinca, M.; Cosgarea, R.; Jonca, N.
Summary: Autosomal recessive congenital ichthyosis (ARCI), a severe and highly clinically heterogeneous group of mendelian disorders of cornification, is the result of mutations in at least nine genes regulating the epidermal barrier functionality. NIPAL4 is the second most frequently mutated ARCI gene. We report two adult patients from a nonconsanguineous family of Romanian origin, who had lamellar ichthyosis. A positive in situ transglutaminase 1 activity assay excluded a putative TGM1 mutation. NIPAL4 sequencing revealed in both patients a new homozygous missense mutation, c.403A>C, affecting a highly conserved amino acid ( p. Ser135Arg ) and predicted to be deleterious according to in silico analysis. In addition to the ARCI features, the patients had caries and partial edentation. Although delay in dental treatment led to caries progression and extraction of secondary teeth, this finding raises the possibility of a deficiency in enamel mineralization due to NIPAL4 dysfunction as an Mg 2+ transporter. Evaluating new patients with ARCI provides fruitful clinical and molecular findings.